Feed the Future Malawi Improved Seed Systems and Technologies Project (MISST): Scaling Out Orange-Fleshed Sweetpotato - International Potato Center (2016)
Within the first two years, MISST enabled over 27,000 households to produce and consume pro-vitamin A rich orange-fleshed sweetpotato (OFSP) varieties. To increase access to clean planting material, we trained more than 40 commercial vine multipliers out of which 15 have actively started selling OFSP planting material, and helped to establish 65 Decentralized Vine Multiplication (DVM) sites. We built the capacity of private sector, government and NGO’s to scale out OFSP technologies.